The left side of the screen Communist and left-wing ideology in Hollywood, 1929-2009 - Herzberg, Bob, 1956- (McFarland & Co., 2011)
"An examination of the careers of communist and liberal actors, screenwriters, playwrights, and directors in Hollywood from the late 1920s to the present, this book uses studio and PCA correspondence, FBI files, film and theater reviews, and other sources to reveal how these artists were concerned with and active in the cinema of social protest"--Provided by publisher.